Anti-tumoral Effect of a Cell Penetrating and Interfering Peptide Targeting PP2A/SET Interaction - Andrini, Laura Beatriz (2020)
Objective: To test cell penetrating and interfering peptide Mut3DPT-PP2A/SET in interaction between serine threonine phosphatase PP2A and its physiological inhibitor, the oncoprotein SET. Materials and methods: Adult male C3H/S-strain mice, 60 days old, were given a graft of breast adenocarcinoma cells (TN60) into subcutaneous tissue. Mut3DPT-PP2A/SET peptide was used to block PP2A and SET oncoprotein interaction. The graft-bearing animals were divided into a control group (injected with saline buffer), and an intervention group injected intraperitoneally with Mut3DPTPP2A/ SET peptide (5 mg/kg) every day from day 5 to day 37. The variables we used to compare the outcome in both groups were tumor size in mm (length×width) and histological changes. In the statistical analysis we used ANOVA and Student-Keuls multiple comparisons test and Tuckey for the post-test analysis. Results: 48 mice were grafted at day 0 with breast UNLP-C3H/S tumor cells, and after randomization, they were assigned to one of the two study groups. At day 5 all mice were injected either with placebo or with the peptide. The treated group showed significant tumor reduction (p<0.07). Histological changes showed presence of apoptosis and necrosis of tumor in treated group. Conclusion: The peptide Mut3DPT-PP2A/SET has demonstrated anti-tumor activity by reduction in vivo of tumor growth becoming a promising future in anticancer therapy.